Degradation variability of facades with ceramic coating on buildings in Brasília, Brazil - Silva, Maykon Vieira; Bauer, Elton (Ambiente Construído, 2024)
Ceramic coating finds are widely used in buildings due to their durability, weather resistance and attractive aesthetics. Over time, these facades are subject to various factors that can cause anomalies, affecting their appearance and performance. Different degrees of protection and exposure to degradation agents, as well as the variability in the quality of materials and construction processes lead to different degradation along the facade. The objective of the research is to study the variability of degradation along the facade, how it appears and which are the main factors responsible. The research is based on a database, developed from inspections of buildings in Brasília, using the Degradation Measurement Method (MMD. The analyzes are based on degradation indicators. The results show that there is variability in degradation resulting from numerous variables. Older buildings have greater extents of degradation. It is observed that there is variability in degradation between the floors of the building’s facade, mainly in relation to the sixth floor and top, showing that the position on the facade is a significant factor in the degradation process. The identification of causes of degradation and the most vulnerable points of the facade allows the development of appropriate design and maintenance strategies.